VD_FINDINFO HC / 2013 / 143 vom 13. Februar 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, LITISPENDANCE, BAIL À LOYER | 59 al. 1 CPC (CH), 59 al. 2 let. a CPC (CH), 59 al. 2 let. d CPC (CH), 60 CPC (CH)